2016
DOI: 10.1101/gad.271288.115
|View full text |Cite
|
Sign up to set email alerts
|

Control of heterochromatin localization and silencing by the nuclear membrane protein Lem2

Abstract: Transcriptionally silent chromatin localizes to the nuclear periphery, which provides a special microenvironment for gene repression. A variety of nuclear membrane proteins interact with repressed chromatin, yet the functional role of these interactions remains poorly understood. Here, we show that, in Schizosaccharomyces pombe, the nuclear membrane protein Lem2 associates with chromatin and mediates silencing and heterochromatin localization. Unexpectedly, we found that these functions can be separated and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
239
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(263 citation statements)
references
References 51 publications
24
239
0
Order By: Relevance
“…Lem2 and Man1 share a MAN1/Src1C‐terminal (MSC) domain at their C‐terminal region, which is conserved in eukaryotic Man1 and Lem2 proteins (Mans et al ., ; Brachner and Foisner, ). The Lem2 MSC domain is required for telomere–NE association (Barrales et al ., ) while the role of the Man1 MSC domain in the telomere–NE association has not been reported. It has also been reported that homologues of Lem2 ( S. cerevisiae Heh1/Src1 and C. elegans LEM‐2) associate with telomeric regions (Grund et al ., ; Ikegami et al ., ), and that loss of Heh1 causes defects in the perinuclear positioning of telomeres and the silent rDNA loci in S. cerevisiae (Mekhail et al ., ; Chan et al ., ).…”
Section: Organization Of Chromatin At the Nuclear Peripherymentioning
confidence: 99%
See 3 more Smart Citations
“…Lem2 and Man1 share a MAN1/Src1C‐terminal (MSC) domain at their C‐terminal region, which is conserved in eukaryotic Man1 and Lem2 proteins (Mans et al ., ; Brachner and Foisner, ). The Lem2 MSC domain is required for telomere–NE association (Barrales et al ., ) while the role of the Man1 MSC domain in the telomere–NE association has not been reported. It has also been reported that homologues of Lem2 ( S. cerevisiae Heh1/Src1 and C. elegans LEM‐2) associate with telomeric regions (Grund et al ., ; Ikegami et al ., ), and that loss of Heh1 causes defects in the perinuclear positioning of telomeres and the silent rDNA loci in S. cerevisiae (Mekhail et al ., ; Chan et al ., ).…”
Section: Organization Of Chromatin At the Nuclear Peripherymentioning
confidence: 99%
“…A conserved HEH/LEM domain INM protein Lem2, which localizes at the nuclear periphery and the SPB (King et al ., ; Hiraoka et al ., ; Gonzalez et al ., ), plays a role similar to Csi1 in stabilizing minichromosomes: lem2 mutant cells show an increased loss of minichromosomes (Tange et al ., ). Despite similar phenotypes of the mutant cells, the roles of Lem2 and Csi1 in centromere–NE association are independent of one another (Barrales et al ., ; Tange et al ., ). Interestingly, loss of minichromosomes in the lem2 mutant is remarkable in a rich medium, suggesting that centromere defects can be changed by environmental conditions, in contrast to the csi1 mutant in which loss of minichromosomes is independent of rich or minimum medium (Tange et al ., ).…”
Section: Organization Of Chromatin At the Nuclear Peripherymentioning
confidence: 99%
See 2 more Smart Citations
“…Because the proteasome is enriched in NM (33) and both the proteasome and the centromere are localized at the inner nuclear membrane (NM) in fission yeast (53,54), it could be the same nuclear compartment that accounts for the high enrichment of the proteasome at the centromere. In fact, NM proteins are reportedly involved in both regulating heterochromatin and anchoring the proteasome to the NM (55,56). Thus, it may be plausible that NM proteins are involved in recruiting the proteasome to the centromere.…”
Section: S Proteasome Involvement In Heterochromatin Spreadingmentioning
confidence: 99%